Interventions used in control group against cupping therapy for chronic nonspecific low back pain: A systematic review and network meta-analysis - Junyan Li; Yuanyuan Jia; Tingting Sun; Zhenmin Bai; Xiaosheng Dong; Xiao Hou (Complementary Therapies in Medicine)
Introduction: The evidence for the effect of cupping therapy on chronic nonspecific low back pain (CLBP) remains controversial, and existing researches didn’t consider outcomes influenced by factor of selection of interventions in control group. This review and network meta-analysis is to compare the effects of diverse interventions in cupping therapy control groups for CLBP, with the objective of identifying the suitable control intervention against cupping therapy for CLBP. Methods: Studies were identified by a comprehensive search of databases, such as PubMed, Embase, Cochrane Library, Web of Science and China National Knowledge Infrastructure (CNKI), up to June, 2024. A total of 10 randomized control trials (RCT) were included in this network meta-analysis (NMA). Results: The results showed that compared with cupping therapy, minimum negative pressure cupping therapy (MNPCT) (SMD = − 0.01; 95 %CI: − 0.92 to 0.89), air circulating cupping therapy (ACCT) (SMD = − 0.05; 95 %CI: − 0.63 to 0.54) and diclofenac (SMD = − 0.13; 95 %CI: − 1.13 to − 0.87) was no significantly different from improvement of pain intensity. But there was significant difference between cupping therapy and D-ibuprofen (SMD = − 1.11; 95 %CI: − 2.08 to − 0.13), paracetamol (SMD = − 1.12; 95 %CI: − 1.80 to − 0.43) or usual care (SMD = − 1.18; 95 %CI: − 2.56 to − 1.06). The order of intervention effect by SUCRA diagram was as follows: cupping therapy (77.7 %) > MNPCT (75.2 %) > ACCT (73.8 %) > diclofenac (68.8 %) > D-ibuprofen (26.3 %) > paracetamol (24.5 %) > usual care (3.8 %). The quality of evidence for network estimates was moderate to very low due to the risk of bias and imprecision. Conclusions: The results of this study suggest that usual care was the least effective in alleviating the pain intensity of CLBP, which might serve as the most appropriate intervention in the control group in cupping-related RCTs. MNPCT and ACCT have similar effects with cupping therapy for CLBP. Future research may be based on some objective clinical outcomes and control interventions with physiological inertia to isolate the true effect of cupping therapy or SCT from psychological biases. Trial registration: The protocol was registered on the international prospective register of systematic reviews (http://www.crd.york.ac.uk/PROSPERO), registration number: CRD42024527513.